A Discretization-Hierarchization Approach to Information Management -- Implications for Digital Earth - Suteanu, Christian (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The paper addresses ways of supporting the Digital Earth project. Highlighting the merits of discretization and analyzing classification-hierarchization operations as forms of discretization, it shows that their rigidity and inertia with respect to change stand in contrast to the flexibility required by Digital Earth, and proposes a path towards solutions. Cette communication présente des façons d’appuyer le projet Digital Earth. En mettant en lumière les mérites de la discrétisation et de l’analyse des opérations de classification et d’hiérarchisation comme forme de discrétisation, cela démontre leur rigidité et leur inertie relativement au changement, qui s’oppose à la flexibilité requise par Digital Earth. Quelques pistes de solutions seront proposées.